PERFORMANCE OF ICT-TB TEST in the Detection of Pulmonary and extra-Pulmonary TUBERCULOSIS - Khan, Nisar; Mian, Ihsanullah; Ullah, Zia; Muhammad, Jan (Journal of Ayub Medical College Abbottabad, 2004)
Background: Tuberculosis is a major public health problem of the developing nations including Pakistan. We need a simple, economical and non invasive test to make an early diagnosis of T.B. in order to avoid the complications. Methods: A study was conducted at the Dept. of Pulmonology, PGMI LRH Peshawar & Ayub Teaching Hospital Abbottabad with the collaboration of Deptt of Pathology KMC Peshawar from Jan 1998 to Dec 2002. A total of 129 patients were included in the study. Out of these 129 patients 52 were pulmonary TB (PTB) smear positive, 30 were PTB smear negative, 30 pleural effusion & 17 were TB lymphadenitis. The control group consisted of 25 non TB patients and healthy subjects. Results: Antibody was detected in 23 of 52 (44%) sputum positive patients, 11 of 30 (36%) sputum negative PTB patients, 10 of 30 (20%) patients of TB pleural effusion and 6 of 17 (35%) patients of TB lymphadenitis. Antibody was detected in none of the control subjects. The overall sensitivity for Pul-T.B. Sputum positive patients was 44%, 36% for sputum Negative Pulmonary TB, 20% for TB pleural effusion and 35% for TB lymphadenitis. The specificity was 100%. Conclusion: ICT-TB is a highly specific, but less sensitive aid in the diagnosis of Pulmonology and extra Pulmonolgy TB.